The study of thermodynamic mechanisms of advection-cooled sea fogs for two cases based on the WRF model - Ye, Xin-Ya; Shen, Fei-Fei; Fei, Hai-Yan; Sun, Qi-Long; Shu, Ai-Qing; Wan, Shen; Chen, He (Frontiers in Earth Science, 2025)
IntroductionSea fog significantly affects maritime transportation and coastal safety. This study investigates the thermodynamic mechanisms driving two persistent sea fog events in China: one along the coast of Zhejiang Province (March 27–April 2, 2018) and another in the Qiongzhou Strait (January 20–26, 2021). Although both events are primarily caused by advection cooling, their underlying thermodynamic structures differ due to varying synoptic and mesoscale conditions.MethodsHigh-resolution numerical simulations were performed using the Weather Research and Forecasting (WRF) model. Supplementary data sources include MICAPS surface observations, ERA reanalysis data, and radiance measurements from the FY-4A satellite. A combination of synoptic background analysis, mesoscale structural examination, and thermodynamic field diagnostics was used to identify the mechanisms of fog formation. The accuracy of fog extent prediction was also evaluated using the FSL (based on relative humidity) and SW99 (based on cloud-water mixing ratio) visibility algorithms.ResultsBoth fog events were driven by advection cooling but exhibited distinct thermodynamic profiles. The Zhejiang case was characterized by warm and moist advection over a cold sea surface, with a pronounced sea-air temperature gradient, a low inversion layer (below 850 hPa), and moderate atmospheric stability. The Qiongzhou Strait case showed a deeper and more stable atmospheric structure, with warm advection extending down to 950 hPa and a discontinuous inversion layer at higher levels, contributing to greater thermodynamic stability. In terms of fog prediction, the FSL algorithm outperformed SW99 in estimating fog coverage, although both had limitations in accurately predicting visibility levels.DiscussionThis comparative analysis highlights the influence of differing synoptic and mesoscale conditions on the formation and evolution of advection-cooled sea fog. The results suggest that regional fog forecasting can benefit from a synergistic thermodynamic-dynamic diagnostic framework. Understanding these differences enhances the ability to forecast fog development under varying meteorological backgrounds.